Correlation of plasma levels of itraconazole with treatment response at 4 weeks in chronic dermatophytosis: Results of a randomised controlled trial. Issue 4 (8th December 2022) - Bhalavi, Hitesh; Shaw, Dipika; Mehta, Hitaishi; Narang, Tarun; Sachdeva, Naresh; Shafiq, Nusrat; Rudramurthy, Shivaprakash M.; Dogra, Sunil
Abstract: Background: Itraconazole in varying doses and duration is being frequently used for the management of dermatophytosis. There is a scarcity of studies on the bioavailability of various itraconazole brands available in the market. Aims and Objectives: The aim of this study was to determine the plasma concentration of itraconazole of various brands and its correlation with clinical efficacy in chronic dermatophytosis. Materials and Methods: One hundred patients with chronic dermatophytosis with age >18 years were studied at the outpatient clinic of our tertiary care hospital. Plasma itraconazole level was estimated on Week 2 and Week 4 after randomly dividing the patients into Groups A, B and C who received cap itraconazole 100 mg twice a day of innovator, multinational and local generic brands, respectively, for 4 weeks. Both efficacy (cure, partial cure or no cure), safety and recurrence were compared between the three groups. Results: At 4 weeks, number of patients classified as 'cured' were 10/26 (38.4%) in Group A, 5/22 in Group B (22.7%) and 3/21 (14.2%) in Group C ( p  = .002). Mycological cure rates at Week 4 in Groups A, B and C were 21 (80.8%), 17 (81.0%) and 5 (26.3%), respectively ( p  = .006). Plasma levels of itraconazole were comparable between the three groups at Week 2 and Week 4. No statistically significant correlation was found between itraconazole levels and treatment response in any of the groups at 4 weeks. Incidence of adverse effects and recurrence rates was also similar among the three groups. Conclusion: Cure rates for chronic dermatophytosis were poor with all three itraconazole brands at 4 weeks of treatment. Higher cure rates were obtained with innovator drug as compared to multinational and local generic brands at 4 weeks. Plasma levels of the three drugs were however similar, indicating that factors other than serum bioavailability are at play in determining response of chronic dermatophyte infections to oral itraconazole.